Motoric cognitive risk syndrome as a predictor of incident disability: A 7 year follow-up study - Bai, Anying; Bai, Weimin; Ju, Hepeng; Xu, Weihao; Lin, Zhanyi (Frontiers in Aging Neuroscience, 2022)
Background: Though motoric cognitive risk syndrome (MCR) shares risk factors with disability, whether it predicts disability remains understudied. This study aims to examine the association between MCR and incident disability. Methods: MCR was defined as subjective cognitive complaints and objective slow gait speed. Two subtypes of MCR were defined by whether memory impairment (MI) was also present, MCR-MI and MCR-non-MI. Incident activities of daily living (ADL) disability and instrumental activities of daily living (IADL) disability were outcome measures. Multiple logistic regression analysis was used to assess the independent effect of MCR at baseline on the odds of ADL/IADL disability at a seven-year follow-up. Results: Among the subjects who were not disabled at baseline and followed for seven years, 34.66% reported incident ADL disability, and 31.64% reported incident IADL disability. Compared with participants without MCR at baseline, those with MCR had 59% increased odds of incident ADL disability (OR=1.59, 95% CI: 1.20–2.10) and 47% increased odds of incident IADL disability (OR=1.47, 95% CI: 1.14–1.90) after seven years. MCR-non-MI was associated with a 52.7% increased risk of ADL disability and a 35.8% increased risk of IADL disability. MCR-MI was associated with an even higher risk of ADL disability (OR=1.84, 95% CI: 1.03–3.29) and IADL disability (OR=2.31, 95% CI: 1.27–4.17). Conclusions: MCR is an independent risk factor for both incident ADL and IADL disability. MCR-MI predicts a higher risk for disability than MCR-non-MI. Early identification of MCR among older adults is recommended and may decrease the future risk of disability.